Corporate Image and Innovation as Strategic Drivers of Consumer Decisions in Islamic Banking - Junaedi, Ahyar (International Journal of Entrepreneurship and Sustainability Studies, 2025)
This study investigates the simultaneous effects of corporate image and product innovation on customer decision-making in the context of Islamic banking. Focusing on PT Bank Syariah Indonesia, Branch Palangkaraya, the study draws data from 100 respondents using a structured questionnaire and applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among key variables. The results indicate that both corporate image and product innovation have a significant and positive impact on customer decisions, with product innovation exhibiting a slightly stronger effect. Together, these two variables explain 76.8% of the variance in customer decision-making, indicating a robust model. These findings emphasize the strategic role of corporate reputation and continuous product innovation in influencing consumer behavior in the Islamic financial sector. The research provides empirical evidence that integrating reputational elements, such as professionalism, trust, and Shariah compliance, with innovative offerings enhances customer engagement and decision-making. This is particularly relevant in today’s competitive banking landscape, where customers are increasingly influenced by the availability of modern financial services and strong brand credibility. The study makes important contributions to both theory and practice. Theoretically, it enriches the strategic management literature by presenting a dual-variable approach that addresses a gap in Islamic banking research, where corporate image and innovation have often been studied in isolation. Practically, the study offers actionable insights for banking practitioners and policymakers aiming to boost customer acquisition and loyalty through integrated branding and innovation strategies. The context of Palangkaraya also adds value by highlighting consumer behavior in a growing yet under-researched regional market.